Description of a new species of Caenotus Cole (Diptera: Scenopinidae) from Baja California Sur, Mexico, with a review of the genus - Metz, Mark A. (Zootaxa, 2003)
A new species of Caenotus Cole is described from Baja California. The current knowledge of the systematics and states of morphological characters with putative phylogenetic importance within the genus are discussed and summarized. One species Caenotus thompsonii Evenhuis is placed in synonomy with Brachylinga baccata Coquillett (Diptera: Therevidae).